Ecological Condition, Degradation Status, and Restoration Priorities for Sustainable Mangrove Conservation in the Kepetingan Coastal Landscape, East Java, Indonesia - Izzatul Fakhiroh; Ali Ogla (Journal of Academic Biology and Biology Education, 2025)
Purpose of the study: This study aimed to assess the ecological condition, degradation status, and environmental suitability of mangrove ecosystems in the Kepetingan Coastal Area, East Java, Indonesia, and to identify stakeholder-based restoration priorities to support sustainable mangrove landscape conservation and ecosystem recovery. Methodology: Field surveys were conducted at three sampling stations representing settlement, estuarine, and abandoned aquaculture pond areas. Mangrove vegetation was assessed using the line transect–plot method. Vegetation density, frequency, dominance, and Importance Value Index (IVI) were analyzed. Water temperature, salinity, dissolved oxygen, and pH were measured using field instruments. Mangrove degradation status was evaluated using critical mangrove land assessment criteria, while restoration priorities were determined through SWOT analysis based on stakeholder interviews and questionnaires. Main Findings: Five mangrove species were identified, with Rhizophora stylosa, Avicennia marina, and Bruguiera gymnorrhiza showing the highest ecological importance. Tree density ranged from 300–600 trees ha⁻¹, indicating degraded ecosystem conditions. The critical land assessment produced a score of 285, classifying the area as critical mangrove land. Mangrove cover declined from 140.54 ha in 2010 to 109.20 ha in 2015. Environmental parameters remained suitable for restoration, and SWOT analysis identified the Weakness–Opportunity (WO) strategy as the highest restoration priority. Novelty/Originality of this study: This study integrates ecological condition assessment, environmental quality evaluation, mangrove degradation analysis, and stakeholder-based SWOT planning within a single restoration framework. The approach provides a comprehensive basis for determining restoration priorities and contributes to the development of integrated mangrove landscape conservation strategies in degraded tropical coastal ecosystems.